Human Resource Information System Berbasis Website (Studi Kasus PT. Begawan Avaloka Indonesia Konsultama) - Syahril Hidayat; Munawaroh (CV. Multi Kreasi Media, 2024)
Management of leave and retirement data that is still manual causes several problems, such as employees not knowing the number of remaining leaves. Application for retirement and application for leave still use paper forms that require various stages until the report is validated. This study aims to develop a web-based Human Resource Information System design at PT. Begawan Avaloka Indonesia Konsutama uses the PHP programming language and the Laravel framework as a framework, as well as an adaptive and communicative waterfall method. In this case, a web-based information system for applying for employee leave was developed using the PHP programming language and the Laravel framework as the framework, as well as the waterfall method as the method and the testing system using the Black Box and White Box. The results of this study with the developed information system, employees can easily find out the number of remaining leaves and apply for leave and retirement online, increase the effectiveness and efficiency of applying for employee leave and retirement, as well as security of leave and retirement data. This research is expected to provide benefits for the company.